Lista de répteis do Brasil: padrões e tendências - Costa, Henrique C.; Guedes, Thaís B.; Silveira Bérnils, Renato (Herpetologia Brasileira, 2026)
We present the list of Brazilian reptiles for the year 2021. Brazil has 848 species of reptiles whose presence is confirmed within its borders: 38 Testudines, 6 Crocodylia, and 804 Squamata (82 amphisbaenians, 292 lizards, and 430 snakes). If subspecies are counted, the number increases to 885 taxa. This is the third richest reptile fauna in the world. A total of 399 species (47%) of Brazilian reptiles are endemic to the country, mainly amphisbaenians (79.2%), followed by lizards (55.5%), snakes (38.4%), and chelonians (18.4%). Mato Grosso, Bahia, and Pará are the richest states in number of species and species+subspecies. Bahia, Minas Gerais, and São Paulo have the greatest numbers of Brazilian endemic species. We also note nomenclatural changes, species and subspecies included or excluded for the country, and for federative units since the last checklist. As a new feature in this version, we present a section about patterns and trends of advances in the knowledge of Brazilian reptiles through graphs and maps, and a section of notes about the recently published Atlas of Brazilian Snakes.